INTELLECTUAL CAPITAL VALUE AND DISCLOSURE OF INTELLECTUAL CAPITAL ON FIRM VALUE - Muslim Muslim; Hajering Hajering; Yaya Sonjaya; Victor Pattiasina (Jurnal Ilmiah Akuntansi Peradaban, 2023)
The purpose of this study was to determine the effect of the value of intellectual capital and disclosure of intellectual capital on the company value of state-owned enterprises which are listed on the Indonesian stock exchange partially. The type of data used in this study is quantitative data in the form of values or numbers obtained from financial reports. The source of data in this research is secondary data. The population in this study are state-owned companies listed on the Indonesia Stock Exchange during the period 2015 -2019. By using the purposive sampling method, the total sample in this study is 45 data from 9 companies. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, classic assumption tests (normality test, heteroscedasticity test, multicollinearity test, autocorrelation test), and testing all hypotheses through the partial test (t test) and coefficient test determination. The research findings lead to several concrete conclusions. Firstly, the study reveals a significant negative effect of intellectual capital value on firm value for state-owned companies in Indonesia. This suggests that intellectual capital alone does not guarantee an increase in firm value. Secondly, the research demonstrates a significant positive effect of intellectual capital disclosure on firm value. Active disclosure of intellectual capital information positively influences stakeholders' perceptions and builds confidence in the company's potential, ultimately enhancing firm value Keyword: Intellectual capital; disclosure of intellectual capital; the value of the company